Analysis of Abstracts in Scientific Papers Written in English Using Corpora - Rodrigo Tovar Viera (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Research article abstracts are the gateways to communicate the research findings. This function and the significant contribution in disseminating the knowledge production have been the issue of academic research studies across disciplines. Abstracts, indeed, after titles, are the most read section freely available online. However, despite the impressive output contribution to the academic discourse community, both national and international and much research developed on abstracts, investigations particularly contrasting article abstracts published in Ecuadorian and North-American journals are scarce. The study examines the rhetorical organization and the linguistic realizations of abstract written in four disciplines, by first identifying the move structure and then their linguistic realizations, including verb tense, clauses, modals and stance markers. The contrastive analysis of English and Spanish texts is based on a corpus of 120 abstracts from the fields of humanities and science. Results showed that abstract published in Ecuadorian and North-American journals from four disciplines do put more emphasis on purpose, method, and product (results) in order to introduce the new knowledge. Throughout the corpus present, past tense, and hedges were the most frequent categories. The present tense commonly occurred in M1-M2-M5. The similarities and differences in the rhetorical organization and linguistic realizations of abstract moves might be attributed to the context of publication; however, such rhetorical and style choices remain quite unclear, in terms of conventional patterns or authors’ preferences.